The Utilization of Organic Waste Chicken Cage Fertilizer on the Growth of Cocoa (Theobroma Cacao L.) - Lukman (GoAcademica Research & Publishing, 2021)
The agricultural sector is the largest contributor of organic waste that can be recycled as useful things, among others, used as organic fertilizer. This study aims to determine the effect of agricultural waste organic compost on the growth of Cocoa (Theobroma Cacao L.) plants. The analysis results of the materials to be applied are N-total: 0.27% P2O5: 3.20%, K2O: 1.63%, and C-Organic: 17.40%, then the research data were analyzed using a Randomized Block Design (RAK) which consists of 6 levels of treatment, namely: C0 = no fertilizer, C1 = soil + 20 g compost polybag-1, C2 = soil + compost 40 g. polybag-1, C3 = soil + compost 60 g. polybag-1, C4 = soil + compost 80 g. polybag-1, C5 = Soil + compost 100 g. polybag-1. Each experiment was repeated three times, so there were 90 experimental units. Observation parameters were plant height, number of leaves, and stem diameter. The results showed that, giving 100 g of organic waste compost polybag-1 gave better results on the growth of cacao seedlings, with a plant height of 29.61 cm, number of leaves 11.73 strands, and stem diameter of 3.38 mm. From this research, it can be concluded that it will produce better results if organic waste is managed properly.